Towards a circular bioeconomy. Volatile fatty acid platform for biowaste recycling - Michels, Jochen (2020)
Resources in general are not infinitely available, and also renewable resources if consumed outside their normal replacement cycles become scarce. Therefore, the establishment of a circular bioeconomy must respect natural systems and replacement cycles of organic carbon thereby reducing environmental pressure of human consumption. Upcycling of side and biowaste streams towards added value compounds represents hereby a critical aspect reducing land system change and fertilizer use for biomass supply for the bioeconomy. The development of a Volatile Fatty Acids Platform (VFAP) represents an important cornerstone for the upcycling of heterogenous municipal biowaste streams.